2007
DOI: 10.1111/j.1600-0846.2007.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of optical coherence tomography in non‐invasive characterization of skin vascular lesions

Abstract: The analysis of vascular lesions by OCT provides a new insight into non-invasive diagnosis and can be helpful in the selection of the most appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 13 publications
2
24
0
2
Order By: Relevance
“…These details may have some applicability in laser treatment of haemangiomas, and future studies to explore OCT imaging of haemangiomas are necessary. Previous studies demonstrated a 3D OCT image of a similar lesion [57] and in another study OCT images matched histology of haemangiomas [58]. The use of Doppler OCT may have a potential for identifying feeding vessels and prognosis estimation in capillary haemangiomas and vessels in general during laser treatment, which has been demonstrated using Doppler US [59], and in a study of one port-wine stain by Doppler OCT [60].…”
Section: Haemangiomasmentioning
confidence: 75%
“…These details may have some applicability in laser treatment of haemangiomas, and future studies to explore OCT imaging of haemangiomas are necessary. Previous studies demonstrated a 3D OCT image of a similar lesion [57] and in another study OCT images matched histology of haemangiomas [58]. The use of Doppler OCT may have a potential for identifying feeding vessels and prognosis estimation in capillary haemangiomas and vessels in general during laser treatment, which has been demonstrated using Doppler US [59], and in a study of one port-wine stain by Doppler OCT [60].…”
Section: Haemangiomasmentioning
confidence: 75%
“…OCT provided optical biopsies based on the detection of inhomogeneities such as roundish-shaped or oval signal-poor cavities. The signal-poor regions indicating vascular structures sharply demarcate from the signal-rich microenvironment [11]. The pre-therapeutic knowledge of the lumen and the depth of the vessels can optimize the treatment of hemangiomas and vascular malfunctions.…”
Section: Resultsmentioning
confidence: 99%
“…OCT systems have been used in dermatology since the 90s mainly for experimental and clinical studies. The morphology and epidermal thickness of normal skin has been investigated [8] as well as bullous diseases [8], psoriasis, contact dermatitis [9], melanocytic lesions [10], and vascular lesions [11]. In contrast to ophthalmology, the technique is not yet applicable for routine diagnostics in dermatology and is still under development.…”
Section: Biophotonicsmentioning
confidence: 99%
“…However, in the present study, it was not possible to find significant differences between the formulations and control. As non-invasive equipment, Cutometer ® has made it possible to study the mechanical properties of skin and evaluate the effect of cream when used in certain conditions (28). Although the results were not considered statistically significant, they indicate that the effects of chamomile extract after single or 2-and 4-weeks of daily applications were more pronounced on hydration properties of skin.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, no presente estudo, não foi possível determinar diferenças significativas entre as formulações e o controlo. Como equipamento não-invasivo, o Cutometer ® tornou possível estudar as propriedades mecânicas da pele e avaliar o efeito do creme nas condições de utilização (28). Embora os resultados obtidos não tenham sido considerados estatisticamente significativos, estes indicam que os efeitos do extracto de camomila, após única aplicação ou 2 -e 4 semanas de aplicação diária foram mais pronunciados nas propriedades de hidratação da pele, o que pode implicar que seja possível encontrar efeitos significativos sobre as propriedades mecânicas da pele, se os tratamentos forem aplicados por um período de tempo mais longo.…”
Section: Discussionunclassified